Unveiling the Veiled: Unwed Teenage Pregnancy and its Impact on the Malaysian Population - Eid, Iyad Muhammad; Jalal Nori, Abdulwahed; Mohd Zin, Najibah; Ra'ees, Wahabuddin (2021)
This paper aims to address teenage pregnancy out of wedlock in the Muslim Malay community in Malaysia. Since its independence in 1957, Malaysia has been experiencing dramatic economic and social transformations. Consequently, the living conditions of the Malays have greatly improved, and modernity has made them fully engaged in materialistic lifestyles, compromising their conservative Islamic values which used to be the basis of organizing of their social relationships. The function of the value system is gradually weakening while critical social problems, such as teenage pregnancy out of wedlock, are emerging in the society. The present research attempts to discuss the factors causing teenage pregnancy, examine the impacts of this problem on the teenagers themselves and investigate how families and teenagers deal with it to avoid baby dumping. Using a qualitative approach, this case study conducted in-depth semi-structured interviews with thirty Muslim Malay teenagers who experienced illegal pregnancy. The research took place in two organizations operating as rehabilitation centres to assist the girls lead more productive life in the future. Collected data were transcribed and analysed by thematic analysis method. The findings showed that the absent role of family, media, peer pressure and other factors contributed to the occurrence of teenage pregnancy. Further, the study found out that the organizations lack financial resources and professional capabilities to play more effective roles in controlling the problem. Funded by the fundamental research grant scheme (FRGS), this study seeks to design and implement a social framework to control this problem.